Bacterial safety of blood components–a congress review of the ISBT transfusion‐transmitted infectious diseases working party, bacterial subgroup. (18th March 2019) - Ramirez‐Arcos, Sandra; McDonald, Carl; Deol, Parampal; Kreuger, Aukje L.; Patel, Nidhi; Pidcoke, Heather; Prax, Marcel; Seltsam, Axel; Stassinopoulos, Adonis; ,
Abstract : The ISBT Working Party on Transfusion‐Transmitted Infectious Diseases, Bacterial Subgroup (TTID‐WP‐BS) held a meeting during the 2017 ISBT Congress covering topics on safety of platelet components (PC), which are highlighted in this review. The TTID‐WP‐BS along with the Paul Ehrlich Institute have pioneered the development of bacterial strain repositories for PC and red blood cells (RBC) to be used for the validation of detection and pathogen reduction (PR) technologies. Results of the development of the RBC repository strains indicated that six bacterial strains were selected for further testing in international studies, complementing the previous study developed for PC. The THERAFLEX UV‐Platelets PR technology has used the bacterial strain repository for PC to test the effectiveness of the system with data presented in this report. Other PR studies described herein include a report of inactivation of Serratia marcescens by the INTERCEPT Blood System for PC at the levels of the PR claim. Furthermore, a summary of current and future developments of the Mirasol PR system was presented with emphasis on PR in whole blood. Advances in PC screening for bacterial contamination were covered by a comparative study of the BacT/ALERT 3D and BacT/ALERT VIRTUO systems, demonstrating that the latter has a shorter time to detection. Finally, data on septic transfusion reactions involving PC produced in plasma and platelet additive solutions indicated different clinical outcomes and screening results. The topics covered during the TTID‐WP‐BS meeting generated insightful scientific discussions and advanced knowledge, one of the most relevant activities of the Bacterial Subgroup.